Using Some Notions from Ausubel and Cambourne in an EFL Elementary Classroom to Build Up Meaningful Learning (2016)
ABSTRACT: This research project was traced from my interest in leading learners to learn meaningfully, and it was done through the implementation of different notions from two authors relevant in this field. This process was carried out at the female school I.E San José located in Itagüí with girls of second grade exposed to a teaching leading them to meaningless language reproduction. Some strategies in the planning and execution of the lessons were implemented and their effectiveness was evaluated with the analysis of the data collected through observations, exams, a survey, a checklist and an interview. The findings revealed that the changes in teaching lead students to make connections, increase their risk taking and meaningful appropriation of the language.